The Pharmacological Properties of Salvia Essential Oils - Zhiming Fu, Hang Wang, Xiaofei Hu, Zhaolin Sun, Chunchao Han (Journal of Applied Pharmaceutical Science, 2013)
Salvia essential oils isolated by hydrodistillation from the plant’s commercial dried aerial parts(Fig.1)ï¼Œhave powerful biological activity and pharmacological properties. The oils contain more than 100 different bioactive compounds, which mainly include Monoterpene hydrocarbons, Oxygenated monoterpenes, Sesquiterpene hydrocarbons, Diterpenes, Not iso-prenoid compounds and Oxygenated sesquiterpenes. It has a number of pharmacological effects including antimicrobial, antioxidant, anti-cholinesterase, improvement of cognitive performance and mood, reducing work-related stress, anti-mutagenic, anticancer, anti-inflammatory, choleretic activities and so on. The present review focuses on the pharmacological activities of Salvia essential oils.
Keywords: Salvia essential oils, bioactive